Increasing the Efficiency of Synthetic Iron Production by the Use of New Kit Lining - Viktor Alekseevich Kukartsev; Alina Igorevna Trunova; Vladislav Viktorovich Kukartsev; Vadim Sergeevich Tynchenko; Sergei Olegovich Kurashkin; Yadviga Aleksandrovna Tynchenko; Ismael Flores Vivián; Kirill Aleksandrovich Bashmur (Metals, 2023)
The production of synthetic iron castings in Russia comprises 50% of all alloys produced; therefore, increasing their smelting efficiency is an urgent task in the industry. This process depends primarily on the efficiency of industrial frequency induction crucible furnaces using acid lining. In the present study, the properties of quartzite, which forms the basis of such a lining, were investigated. An analysis of the proposed variants for changing the composition of the acid lining for use at temperatures of 1550–1600 °C was conducted. Following the preliminary temperature treatment of raw quartzite, which was then subjected to a sintering regime, we determined the conditions under which it was possible to obtain a phase state, allowing for the operation of the lining at temperatures above 1450 °C. We determined the use of an electrocorundum of two fractions as an additive to the traditional composition of the acid lining. The industrial testing of a new liner composition for the smelting of synthetic cast iron in an induction crucible melting furnace with a single steel scrap-metal filling was assessed, which required the use of an increased amount of carburizing agent. The positive results obtained can be explained by the study of the spent lining, which withstood 345 smelting methods of genophasic rent analysis. The results of the test are based on the results obtained in a study conducted on the finished coating of the product.